TOWARDS THE NEW SOCIAL POLICY: EUROPEANIZATION OF THE NATIONAL POLICY OF FINANCIAL SUPPORT FOR FAMILIES WITH CHILDREN - Tanasijevic, Jelena; Stefanovic, Saša; Perisic, Natalija (Srpska politička misao, 2026)
The paper examines the policy of financial support for families with children as an integral part of social policy in Serbia. Its aim is to present and critically analyze the design, scope, and effectiveness of four key measures of the policy of financial support for families with children –maternity leave, parental allowance, child allowance, and preschool subsidies – and to compare it with contemporary European policy trends. The scientific significance of the paper lies in its contribution to understanding the transformation of the national family-oriented social policies in post-transition contexts and their political implications within social policy reforms. By integrating the political, economic, and social dimensions of financial support measures, it expands existing knowledge on how public policies address demographic challenges, gender equality, and child welfare. The focus is on the coverage and adequacy of targeted cash benefits as well as the development of the national design of parental leaves and its generosity in the process of harmonization with the standards of the European Union. The paper has the potential to inform evidence-based policymaking by offering recommendations for improving financial support measures, strengthening parental equality, and reducing child poverty. The comparative analysis with European Union policies highlights gaps and opportunities for policy harmonization, emphasizing the need for sustainable, inclusive, and investment-oriented approaches to the policy of financial support for families with children in Serbia.
Keywords: social policy; public policy; family support; child welfare; parental leave; child allowance; preschool subsidies